CASH FLOWS, MANAGERIAL OWNERSHIPS AND LEVERAGE EFFECTS ON DIVIDEND POLICY IN INDONESIA - Nurul Khalida Ritonga; Erny Luxy D Purba (Universitas Muhammadiyah Tangerang, 2026)
Dividend policy represents a critical corporate financial decision in emerging markets, where firms often face liquidity constraints, concentrated ownership structures, and heightened economic uncertainty. Variations in dividend distribution among Indonesian manufacturing firms during the post-pandemic recovery period suggest that internal financial conditions and capital structure play an important role in shaping dividend policy decisions. This study aims to examine the effects of operational cash flow, free cash flow, managerial ownership, and leverage on dividend policy in manufacturing companies listed on the Indonesia Stock Exchange during the 2022–2024 period. This research employs a quantitative approach using panel data from 77 manufacturing firms selected through purposive sampling, resulting in 145 firm-year observations after data screening and transformation. Multiple linear regression analysis was conducted using IBM SPSS Statistics 30, supported by classical assumption and hypothesis testing. The empirical results indicate that free cash flow has a positive and statistically significant effect on dividend policy, with a regression coefficient of 0.766 and a t-value of 3.717 (p < 0.001). Leverage shows a negative and significant effect, with a coefficient of −0.182 and a t-value of −2.239 (p = 0.027). In contrast, operational cash flow and managerial ownership do not exhibit significant effects, as their significance values exceed 0.05. Simultaneously, all independent variables significantly influence dividend policy, as indicated by an F-value of 5.286 (p < 0.001), although the model explains a relatively limited proportion of variance with an R-squared value of 0.131. These findings suggest that dividend policy in Indonesian manufacturing firms is primarily determined by the availability of free cash flow and leverage levels, emphasizing the importance of effective cash management and prudent capital structure decisions in sustaining dividend payments.